LITERATUR REVIEW: ANALISIS KLASIFIKASI PENYAKIT TANAMAN KEDELAI MENGGUNAKAN DECISION TREE - Akhmad Alvi Sahri; Aly Furqaan Abdurrafi; Calvin Maulana Ersa; Fitra Rio Ramadan; Perani Rosyani (CV. Multi Kreasi Media, 2024)
This study aims to conduct a comprehensive review of the application of the decision tree algorithm in classifying diseases in soybean plants. The decision tree algorithm was chosen for its ability to produce interpretable models and its efficiency in handling large and complex datasets. Through an in-depth analysis of existing studies, this research is expected to provide further insight into the use of decision trees in agriculture, particularly in diagnosing diseases in soybean plants. Additionally, this review will explore recent research trends, challenges faced, and potential future developments in this field.